2019
DOI: 10.1002/iub.2068
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hedgehog ligands in human simple steatosis may protect against nonalcoholic steatohepatitis: Is TAZ a crucial regulator?

Abstract: The conversion of simple steatosis into nonalcoholic steatohepatitis (NASH) in patients with nonalcoholic fatty liver disease (NAFLD) has attracted many attentions in recent years. The role of the hedgehog (HH) pathway in the regulation of lipogenesis has been addressed in the literature. This study aimed to investigate the levels of the sonic hedgehog (SHH) and Indian hedgehog (IHH) ligands and the correlation of these ligands with levels of proteins involved in the transforming growth factor‐β1 (TGF‐β1) path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Conversely, the excessive expression of TAZ in hepatocytes causes an increase in histological characteristics of NASH (21). Further investigation revealed that there was a direct and significant relationship between TAZ expression and HH ligands in the liver tissue (9). The results of our recent study are in line with those of other studies that highlighted the effect of TAZ activity on the expression of HH ligands expression.…”
Section: Yap/taz Signaling Pathwaysupporting
confidence: 89%
See 3 more Smart Citations
“…Conversely, the excessive expression of TAZ in hepatocytes causes an increase in histological characteristics of NASH (21). Further investigation revealed that there was a direct and significant relationship between TAZ expression and HH ligands in the liver tissue (9). The results of our recent study are in line with those of other studies that highlighted the effect of TAZ activity on the expression of HH ligands expression.…”
Section: Yap/taz Signaling Pathwaysupporting
confidence: 89%
“…TAZ and YAP proteins are the ultimate goal of the Hippo pathway (18). Interestingly, in our recent study, TAZ expression in the liver tissue with SS, consistent with changing the level of HH ligands, was significantly lower than that of the control group (9). In some previous studies, it was suggested that the induction of TAZ expression is not a common feature of chronic liver disorders, and its expression is largely limited to those that are associated with steatosis, inflammation, and fibrosis (19,20).…”
Section: Yap/taz Signaling Pathwaysupporting
confidence: 55%
See 2 more Smart Citations
“…However, there was no significant correlation between the expression of TAZ and IHH. In our previous study, we showed that the expression of TAZ was significantly correlated with the expression of Hh ligands in patients with simple steatosis . Also, a recent study has shown that IHH and OPN levels are increased in a TAZ‐dependent manner in animal models of NASH disease .…”
Section: Discussionmentioning
confidence: 88%